Physical illnesses among psychiatric outpatients in a tertiary care health institution: A prospective study - Singh, Gurvinder Pal (Medknow Publications, 2006)
BACKGROUND: The recognition of physical illnesses by mental health professionals has important clinical implications. AIM: This study aimed to find the nature and prevalence of associated physical illnesses in psychiatric outpatients. METHODS: Two hundred fifty consecutive psychiatric outpatients who fulfilled the inclusion criteria of the study were assessed in detail for associated physical illnesses. A conclusive physical diagnosis was based on the clinical history, general physical examination and investigation reports. RESULTS: Forty-eight per cent of the patients were found to have associated physical illnesses. In about one-fifth of the total sample (n=51; 20.4%) the associated physical illness was diagnosed for the first time. Hypertension (29.1%), respiratory diseases (15%), anaemia (12.5%), diabetes mellitus (10%) and liver diseases (5.8%) were some common physical illnesses found in these patients. CONCLUSION: Common physical illnesses of psychiatric patients can be detected mostly by a careful history-taking checklist and physical examination. Psychiatrists must inculcate the habit of conducting a general physical examination of their psychiatric patients.